STUDENTS’ PERCEPTION AND MOTIVATION TOWARD THE USE OF TWO STAY TWO STRAY IN ENGLISH LEARNING FOR ECONOMICS STUDENTS - Musdalifah; Muhammad Fahri Jaya Sudding; Citra Dwi Safitri; Surya Anantatama Sembiring; Andi Kamariah (Program Studi Pendidikan Bahasa Inggris, 2025)
This qualitative study examines students’ perceptions and motivation toward the use of the Two Stay Two Stray (TSTS) technique in English for Economics classrooms. Data were collected through semi-structured interviews to students from Economics faculties. The results indicate that students generally perceive TSTS as an engaging and enjoyable method that enhances their understanding of English materials through peer explanation, interaction, and collaborative learning. Most participants stated that TSTS made complex concepts easier to grasp, increased their participation, and allowed them to learn new vocabulary and communication skills in a more relaxed environment. In terms of motivation, the technique encouraged students to prepare before class, boosted their confidence in speaking, and reduced anxiety compared to traditional lecture-based teaching. However, several challenges were noted, including limited time for explanation, uneven group roles, and the need for clearer instructions. Despite these constraints, students strongly recommended the continued use of TSTS and suggested improvements in time management, group allocation, and the addition of games or ice-breaking activities to enhance engagement. The study concludes that TSTS is an effective and motivating collaborative strategy for teaching English for Economics.